Sultan Alp Arslan’ın Liderlik Vasıfları - Kesik, Muharrem (FSM Vakıf Üniversitesi, 2014)
Büyük Selçuklu Devleti Sultanı Alp Arslan, Türk ve Dünya tarihinin önde gelen hükümdarlarından biridir. Saltanat sürdüğü 1063-1072 yılları arasındaki dönemde çok büyük başarılar elde etmiştir. Hiç şüphe yok ki bu başarılar arasında en önemlisi 1071 yılında kazandığı Malazgirt Savaşı’dır. Zaferin kazanılmasında sultana yardımcı pek çok etken olmakla birlikte, Alp Arslan siyasî ve askeri lider olma vasıflarını en belirgin bir şekilde burada göstermiştir. Bu üstün özelliklerin savaşın kazanılmasında oynadığı rol büyüktür. İşte bu nedenle Alp Arslan’ı büyük bir hükümdar ve kumandan yapan liderlik özelliklerini bu çalışma ile ilgililere ve ilim alemine kaynaklara dayalı bir şekilde sunmaya çalışacağız.

Sultan Alp Arslan of the Great Seljuk State is one of the foremost rulers of Turkish and World history. During his reign as sultan from 1063 to 1072, Alp Arslan achieved many successes but doutless the most important one was his victory at the Battle of Manzikert in 1071. Although there were many factors that aided the sultan in gaining this victory, here is where Alp Arslan demonstrated most clearly his political and military qualities. These superior characteristics played a major role in winning the battle. For this reason, in this study we will endeavor to identify the leadership characteristics that made Alp Arslan a great ruler and commander and present our source-based results to those who are interested and to the scholarly world at large.
Sultan Alp Arslan’s Leadership Characteristics
Keywords: Alp Arslan; Büyük Selçuklu Devleti; Malazgirt Savaşı; Liderlik; Kumandan; Great Seljuk State; The Battle of Manzikert; Leadership; Commander